Estimating Profitability of Islamic Banking in Indonesia - Agus Widarjono (Jurnal Keuangan dan Perbankan, 2018)
The Islamic banking industry in Indonesia had experienced rapid growth since the government passed the Islamic banking law in 2008. Although growing fast but the market share of Islamic banking was still low. To increase the market share of Islamic banking, it was necessary to encourage Islamic banking performance. One of the performances of Islamic banking investigated in this study was profitability. We examined the profitability of Islamic banking using both internal and external factors. The method used to estimate the profitability of Islamic banking was the Autoregressive Distributed Lag Model (ARDL) method with monthly data. The estimation results showed that both internal and external factors affect the profit of Islamic banking. Asset, FDR, efficiency, and NPL affect profitability. An important variable affecting profitability were the bad financing (NPF). While the external factor influencing the profit of Islamic banking was the exchange rate and inflation. The implication of this result was that Islamic banking must be able to manage well the bad financing. Since NPF also depends on macroeconomic conditions, the government must be able to manage macroeconomic performance well such as stabilizing the exchange rate.JEL Classification: G21, G24DOI: https://doi.org/10.26905/jkdp.v22i3.2197